Management practices in the implementation of driving school program at senior high school: A phenomenological study - Putra, M. Rusni Eka; Marianita, Marianita; Prananosa, Ahmad Gawdy; Erwandi, Rudi (UIN Raden Mas Said Surakarta, 2024)
The Driving School program has become a prominent subject in the context of the Independent Curriculum's implementation. While substantial research has been conducted on its execution, studies specifically examining the management processes remain scarce. This study aims to investigate the management of the Driving School program at the senior high school level. Employing a phenomenological approach, the research was conducted at SMAN 5 Lubuklinggau, South Sumatera, Indonesia. The participants included the principal, vice principals, facilitator teachers, alumni, teaching staff, and school administrative personnel. Data were collected through interviews and analyzed using an interactive model for qualitative data. The findings revealed that effective management of the program involves a comprehensive approach encompassing planning, organizing, implementation, and evaluation. Key areas of focus include: 1) student management, from enrollment to graduation; 2) the professional development and performance of teaching and administrative staff; 3) infrastructure and facilities management; 4) financial management; 5) curriculum development; and 6) fostering community partnerships. The study suggests the establishment of a detailed procedural framework, such as Standard Operating Procedures (SOP), to guide future program implementation. Additionally, future research could explore the effectiveness of these management procedures in achieving the program's overarching objectives.